Analysis Of Farming And Agroindustry Of Hanjeli (Coix Lacryma Jobi L.) - Hidayah, Mutiara; Masithoh, Siti; Novita, Ita (JURNAL AGRIBISAINS, 2024)
This study aims to determine the characteristics of hanjeli farmers in Waluran Mandiri Village, Waluran Subdistrict, to determine the feasibility of hanjeli farming in Waluran Mandiri Village, Waluran Subdistrict, and to determine the agroindustry of processed hanjeli in Hanjeli Tourism Village, Waluran Mandiri Village, Waluran Subdistrict. The analysis method used in this research is Descriptive Analysis and Quantitative Analysis. Agro-industry made from hanjeli plants is part of the production of the Hanjeli Tourism Village in Waluran Mandiri Village, Waluaran District, which is managed by KWT Mekar Mandiri. The main ingredients for processed agro-industry use all types of hanjeli plants. The products produced from this hanjeli plant can be consumed and cannot be consumed. The types that can be consumed are glutinous hanjeli and hanjeli batok, which are usually processed into foods such as rengginang, sponge cake, supplements, porridge and several other types. For stone type hanjeli plants, they are usually used as accessories such as necklaces, prayer beads bracelets, and key chains. The results obtained from research with an average land area of 0.521 ha resulted in hanjeli farming income of Rp.768,037 with receipts of Rp.3,408,000 and resulted in total costs of Rp. 2,639,963 during one planting production cycle (6 months). The amount of R / C on hanjeli crop farming is 1.29.